2010
DOI: 10.1097/ncc.0b013e3181b4ab8f
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Surviving Cancer for Latino Adolescents and Emerging Young Adults

Abstract: Background Adolescents and young adult (AYA) survivors of cancer are an understudied population with unique developmental and medical needs that extend well beyond their active treatment. Survivors diagnosed as AYAs may experience both physical and emotional late effects. In particular, the experiences of Latino cancer survivors have not been explored. Objective The purpose of this study was to conduct interviews with AYA Latino cancer survivors to inform professionals working with these survivors. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 13 publications
2
59
0
2
Order By: Relevance
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…26,27 Despite hardship on the family, many YASCC developed closer and stronger relationships with family members through the cancer experience. 28,29,32,36 Survivors reported receiving emotional and physical support from their parents who acted as facilitators to their care. 25 However, in some cases, the increased family bond may have contributed to impaired autonomy for the survivor.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations